(untitled) (Collection of scientific works «Modern structures of metal and wood», 2019)
The article describes the experience of installing a metal 146 meter conveyor gallery. According to the project, the gallery should be arranged above the railway tracks, without interrupting the operation of railway transport for a long time. After analyzing all possible installation variants and considering the possibilities of the contractor, a non-trivial method of carrying out works on the arrangement of the conveyor gallery was chosen. For this purpose, the sliding method was used, which suppose the gallery gradually moved to the arranged supports. As it moves, it changes its design scheme and, as a consequence, efforts in the structural elements. Additional difficulties were added by the fact that the installation was carried out at height of more than 30 m above the level of the railway track, which imposed many restrictions when performing the installation work. To reduce the effort in the elements of the gallery when moving, there was mounted a backbone, 10 m long to its edge. In a case that the design scheme of the gallery has been changing several times, a detailed numerical analysis of the behavior of the supports and every elements of the gallery during the installation work by the finite elements software program "LIRA- SAPR" was performed. The calculations took into account additional installation loads and wind loads, the which value was taken from the data from the meteorological monitoring service. Wind speed was up to 10 m / s. Also, using the techniques which was performed in the software, the dynamic characteristics of the gallery were evaluated. Before the installation works there were carried out full-scale tests of the gallery’s structures, where the deflections were measured at the maximum length of the console when pushed. During the tests, the drawing of the gallery was simulated and various mounting cases were checked. Numerical calculations and full-scale tests confirmed the possibility of installation work on the arrangement of the metal conveyor gallery by the chosen method, which was successfully done in 9 days.